Baseline symptoms and neurocognitive performance across collision, contact, and noncontact female high school athletes - Oldham, J. R.; Howell, D. R.; Lanois, C. J.; Berkner, P. D.; Iverson, G. L.; Mannix, R. C.; Meehan, W. P. III (Medicine & Science in Sports & Exercise, 2025)
Purpose Our purpose was to represent a rare cohort of female collision sport athletes and investigate the association between sport type (collision, contact, and noncontact), symptoms, and performance on baseline neurocognitive assessments.